Ketidaksantunan Tindak Tutur Siswa Sekolah Menengah Pertama - Anisa Fitri Syam; Muh. Saleh; Azis Azis (HUMAN: South Asian Journal of Social Studies, 2022)
Abstract: This study aims to: (1) describe the form of impoliteness of locutionary speech acts of class VIIIA SMPN 3 DuaPitue, (2) describe the form of impoliteness of illocutionary speech acts of class VIIIA students of SMPN 3 Dua Pitue, (3) describe the form of impoliteness of perlocutionary speech acts of class students VIIIA SMPN 3 DuaPitue. This type of research is descriptive qualitative research. The focus of this research is the impoliteness of speech acts of locutions, illocutions, and perlocutions of class VIIIA students of SMPN 3 Dua Pitue. The source of research data is the speech of class VIIIA students of SMPN 3 Dua Pitue. The data collection technique was carried out by listening, recording, and note-taking techniques. The results of the study revealed that there were several forms of impoliteness in locutionary, illocutionary, and perlocutionary speech acts of class VIIIA students of SMPN 3 Dua Pitue. The impoliteness of locutionary speech acts consists of forms of impoliteness of locutionary speech acts with positive impoliteness strategies and strategies of withholding politeness. The impoliteness of illocutionary speech acts consists of forms of impoliteness in illocutionary speech acts with negative impoliteness strategies and sarcasm or ridicule impoliteness strategies. The impoliteness of perlocutionary speech acts consists of forms of impoliteness of students' perlocutionary speech acts with direct or direct impoliteness strategies. Keywords: Impoliteness, Speech Acts, Locutions, Illocutions, Perlocutions.